2009
DOI: 10.1016/j.biomaterials.2009.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of prekallkrein–factor XII interactions in surface activation of coagulation by protein-adsorption competition

Abstract: Traditional biochemistry of contact activation of blood coagulation suggesting that anionic hydrophilic surfaces are specific activators of the cascade is inconsistent with known trends in protein adsorption. To investigate contact activation reactions, a chromogenic assay was used to measure prekallikrein (PK) hydrolysis to kallikrein (Kal) by activated factor XII (FXIIa) at test hydrophilic (clean glass) and hydrophobic (silanized glass) surfaces in the presence of bovine serum albumin (BSA). Hydrolysis of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Alternatively, since FXII autoactivation, and subsequent conformer formation, does not exhibit surface area dependence and is efficient even with hydrophobic surfaces, the small surface area of polystyrene test-tubes might have been sufficient to produce small quantities of FXII conformers which in turn trigger the reciprocalactivation route. This finding seems to support earlier results by Kaushik et al (citation) which indicated that prekallikrein hydrolysis is not localized to an activation complex on the procoagulant surface [24]. Either scenario is indicative of the importance of reciprocal-activation and its role as the major aFXIIa generator as shown previously [38].…”
Section: Fxii Contact-activation In the Presence Of Prekallikrein Andsupporting
confidence: 91%
“…Alternatively, since FXII autoactivation, and subsequent conformer formation, does not exhibit surface area dependence and is efficient even with hydrophobic surfaces, the small surface area of polystyrene test-tubes might have been sufficient to produce small quantities of FXII conformers which in turn trigger the reciprocalactivation route. This finding seems to support earlier results by Kaushik et al (citation) which indicated that prekallikrein hydrolysis is not localized to an activation complex on the procoagulant surface [24]. Either scenario is indicative of the importance of reciprocal-activation and its role as the major aFXIIa generator as shown previously [38].…”
Section: Fxii Contact-activation In the Presence Of Prekallikrein Andsupporting
confidence: 91%
“…The principle role is inhibiting FXII contact with activating surfaces, but these proteins also displace FXIIa from an activating surface into solution where FXIIa is involved in the subsequent steps of the plasma coagulation cascade 222 . The importance of protein adsorption competition in contact activation was also observed in moderating interactions between FXII and PK, which are components of the reciprocal-activations 218 . All these observations implicate protein adsorption competition is an important mediator of contact activation and must be included in any comprehensive mechanisms of surface-induced blood coagulation.…”
Section: Blood Coagulation At Biomaterials Interfacementioning
confidence: 95%
“…However, experimental evidence demonstrated that hydrophobic and hydrophilic surfaces have nearly equal autoactivation properties in neat – buffer solution of FXII, i.e. contact activation of FXII is not specific to anionic hydrophilic surfaces in neat buffer 214,218 . In fact, contact activation of FXII in neat-buffer solution exhibits a parabolic profile when scaled as a function of surface energy.…”
Section: Blood Coagulation At Biomaterials Interfacementioning
confidence: 99%
“…Another interesting aspect of protein adsorption to bioceramics is competition adsorption between two or more proteins on the same adsorbent surface [223][224][225]. Leo Vroman firstly observed that fibrinogen preferentially adsorbed onto tantalum surfaces from blood plasma.…”
Section: Multi-protein Competition Adsorption and The Vroman Effectmentioning
confidence: 99%